(untitled) - Gessner, Ira H (Philadelphia, Pennsylvania, 1993)
The book is divided into three sections. Section one describes basic diagnostic skills emphasizing physical diagnosis and simple laboratory tests. The second section presents common general clinical problems in pediatric cardiology as they present to the primary care physician. The third section reviews some specific clinical problems and management issues. The goal of this book is to help the primary care physician provide more accurate, timely, efficient and cost effective care for infants and children with cardiovascular abnormalities
Keywords: cardiovascular diseases,pediatric cardiology,pediatric cardiology; in infant and childhood,case studies,case studies,examinations, questions, etc